Book Review. (1st September 2017) - Nwakanma, Chido B.
Nation as Grand Narrative: The Nigerian Press and the Politics of Meaning, Wale Adebanwi (2016) Rochester, NY: University of Rochester Press, 391 pp., ISBN-13: 9781580465557, h/bk, $125